2008
DOI: 10.1103/physrevb.78.214201
|View full text |Cite
|
Sign up to set email alerts
|

Origin of giant photocontraction in obliquely deposited amorphousGexSe1xthin films and the intermediate phase

Abstract: Obliquely deposited amorphous Ge x Se 100−x thin films at several compositions in the 15% Ͻ x Ͻ 33.3% range and at several obliqueness angles in the 0 Ͻ ␣ Ͻ 80°range at each x were evaporated on Si and glass substrates. Here ␣ designates the angle between film normal and direction of vapor transport. Raman scattering, IR reflectance, and optical absorption measurements were undertaken to characterize the vibrational density of states and optical band gaps. Edge views of films in scanning electron microscopy ͑S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…8. These features uniquely fix the stoichiometry 57 of the Se-rich phase to close to the centroid of the reversibility window (Fig. 6).…”
Section: Giant Photocontraction (Pc) Of Obliquely Deposited Ge X Se 1mentioning
confidence: 84%
“…8. These features uniquely fix the stoichiometry 57 of the Se-rich phase to close to the centroid of the reversibility window (Fig. 6).…”
Section: Giant Photocontraction (Pc) Of Obliquely Deposited Ge X Se 1mentioning
confidence: 84%
“…The exciting radiation of 1.16 eV used in FT‐Raman is near the middle of the optical gap of Ge x Se 100‐ x glasses, and is transparent to melts profiled in the experiments. However, because of the use of a notch filter to suppress the laser line, the low frequency (<100/cm) vibrational densities of states (VDOS) are inaccessible in FT‐Raman experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research of similar systems [10][11][12][13] showed that properties of glasses with Z around 2.67 can be explained with nanoscale phase separation effects. On the other hand, ternary As-Ge-S system, because of a mix of As centered pyramids and Ge centered tetrahedra, promotes chemical disorder and prevents nanoscale phase separation [13] making that systems suitable for investigation of rigidity percolation effects.…”
Section: Introductionmentioning
confidence: 98%